Female white-collar workers remain at higher risk of breast cancer after adjustments for individual risk factors related to reproduction and lifestyle. Issue 9 (29th April 2017) - Kullberg, Cecilia; Selander, Jenny; Albin, Maria; Borgquist, Signe; Manjer, Jonas; Gustavsson, Per
Abstract : Objectives: The aim was to investigate the variation in risk of breast cancer between occupational groups with a focus on white-collar and blue-collar workers and to investigate to what extent the differences were explained by risk factors related to reproduction and lifestyle. Methods: Between 1991 and 1996, 14 119 women born between 1923 and 1950 and residents of Malmö, Sweden, were included in this cohort study. Individual data on risk factors (eg, age, parity, age at first child, months of breast feeding per child, hormonal replacement therapy, physical activity, alcohol consumption, smoking, height and body mass index) and occupational history were assessed using a questionnaire. First-time diagnoses of invasive breast cancer were identified through the Swedish Cancer Registry up until 31 December 2013. Results: A total of 897 women were diagnosed with breast cancer. Analyses adjusted for age showed an increased risk for white-collar workers compared with blue-collar workers and indicated higher risks in the occupational categories: professionals, administrative and bookkeeping than among women in sales, transportation, production and service work. This difference was only marginally attenuated after adjustment for an extensive set of risk factors related to reproduction and lifestyle. Conclusion: Reproductive and lifestyle factors explain only a minor part of the increased risk of breast cancer in white-collar workers. Further studies are needed to investigate the remaining factors for the difference in risk between occupational groups.